Predictors of placement disruptions in foster care. (January 2020) - Vreeland, Allison; Ebert, John S.; Kuhn, Tarah M.; Gracey, Kathy A.; Shaffer, April M.; Watson, Kelly H.; Gruhn, Meredith A.; Henry, Lauren; Dickey, Lindsay; Siciliano, Rachel E.; Anderson, Allegra; Compas, Bruce E.
Abstract: Background: Many children who are removed from a dangerous or neglectful home and placed in state custody subsequently experience additional disruptions while in custody, which can compound the effects of ongoing stress and instability. As such, placement stability has been identified as a critical objective and a key indicator of success for children residing in substitutive care. Objective: To examine the utility of child protective services data in identifying predictors of placement disruption. Participants and setting: The current study examined data from youth in Tennessee state custody who had been assessed using the Child and Adolescent Needs and Strengths (CANS) assessment within 30-days of their first, out-of-home placement. The sample included 8, 853 youth ages 5–19 years old ( M = 13.1; SD = 4.0; 44.8 % female). Methods: Demographics, placement information, and the CANS assessment were collected by the Tennessee Department of Children's Services for all child welfare episodes for children as part of the system's usual standard of care. Bivariate correlation and linear regression models were conducted. Results: Multiple risk indices from the CANS appeared to significantly increase risk of placement disruption, including child internalizing and externalizing symptoms, school difficulties, youth affect dysregulation, and child age. Conclusions: The current findings suggest that data collected as part of standard practice by child welfare workers such as the CANS is both feasible and has utility for identifying sources of risk for placement disruptions and to inform possible targets of intervention to enhance placement stability.